Impact of magnetic resonance imaging on arthroscopic surgeries of knee joint - Sasnur, Prakash; Patwegar, Abdul Qadeer; H. M., Adarsha (International Journal of Research in Orthopaedics, 2019)
Background: Though magnetic resonance imaging (MRI) is popular as a diagnostic tool, questions arise regarding imaging when clinical diagnosis of most internal derangements of knee can be done. Treatment of meniscal and anterior cruciate ligament (ACL) injuries usually involves arthroscopic surgery after MRI. But accurately performed examination with positive signs alone will be justified for arthroscopy directly without MRI. The aims and objectives of this study are to assess the impact of MRI in selecting or excluding cases which genuinely require an arthroscopic surgery. To know whether routine MRI is required pre-operatively in all cases with positive clinical findings. Methods: 60 cases underwent clinical examination of affected knee and a preliminary diagnosis was made. Further they were subjected to MRI. Results of arthroscopy were considered as definitive diagnosis and results of clinical examination and MRI were judged accordingly. Results: Of 60 patients, examination revealed 85% accuracy, 82% sensitivity, 89% specificity for ACL injuries. For medial meniscus 58% accuracy, 66% sensitivity, 48% specificity. For lateral meniscus 55% accuracy, 58% sensitivity, 50% specificity. MRI revealed 73% accuracy, 82% sensitivity, 63% specificity for ACL injuries. For medial meniscus 63% accuracy, 90% sensitivity, 39% specificity. For lateral meniscus 62% accuracy, 79% sensitivity, 50% specificity. Conclusions: Clinical examination is more sensitive, specific and accurate in diagnosis of ACL. MRI is more sensitive but less specific for meniscal injuries. Clinical examination for cruciate injuries can surpass the MRI findings. Arthroscopy can be performed without MRI in single lesion injuries. However, MRI will play a role in meniscal injuries or doubtful cases.